Moisture Dependent: Physical Properties of Baobab Seeds (Adansonia digitata L.) (Agricultural Engineering, 2023)
The research investigated physical properties of baobab seeds to determine suitable equipment for the processing of its seeds. Pods of baobab used in the study were collected at a local farm in Ilorin, North Central Nigeria. Physical properties of the samples, such as moisture contents, mass, axial dimensions, shape indices, true and bulk densities, porosity, angle of repose and surface area were determined. The results showed that physical properties of baobab seeds were stable for moisture content, ranging between 12 to 18% dry mass (dm). The 100 seed mass (g) and geometric mean diameter increased from 0.60 g to 0.62 g and 10.12 to 10.27 mm respectively, in the moisture range of 12 to 18% dm. Other studied ranges of physical properties ranges included: average length (12.22 to 12.63 mm), width (10.10 to 10.28 mm), thickness (8.23 to 8.42 mm,), sphericity, (81.23 to 82.56 mm), surface area (319.42 to 332.53 mm2 ), 50 seed mass (0.60 and 0.62 g), and 1000 seed mass (12 and 12.4 g) within the moisture content range of 12 to 18% dm. The angle of repose of baobab seeds decreased with an increase in moisture content. The maximum value of 29.18o was obtained at 14% moisture content while a minimum value of 24.42o was obtained at 18% moisture. Moisture content had a significant effect on coefficient of friction of baobab seeds on glass, stainless steel, plywood and rubber. In the same moisture range (12-18%), the static coefficient of friction for baobab seeds ranged from 0-739 to 0-905 on stainless steel, 0-960 to 1-190 on galvanized steel, 0-812 to 1-055 on plywood and 0-496 to 0-950 on glass. The least coefficient of friction values were recorded on stainless steel and glass which implies that baobab seeds will move with lower resistance on these surfaces in post-harvest handling. On the other hand, the resistance will be higher on plywood and glass. The data obtained will serve as guide for agricultural and food engineers, food processors and technicians involved in design and construction of post-harvest equipment used for separating, cleaning, milling and other production processes, to which baobab seeds are subjected.